Do pups recognize maternal calls in pomona leaf-nosed bats, Hipposideros pomona?. (February 2015) - Jin, Longru; Yang, Siliu; Kimball, Rebecca T.; Xie, Lifen; Yue, Xinke; Luo, Bo; Sun, Keping; Feng, Jiang
Abstract : Although evolutionary theory predicts that parents should discriminate between their own and others' offspring when levels of parental care are large, in some colonial breeding mammals, strong selective pressure would be expected to drive the evolution of mutual recognition between parents and offspring. Although less well studied than parental discrimination, in both birds and mammals, offspring discrimination of parents has also been documented. Nocturnal bats depend heavily on acoustic signals for communication, although little is known about whether bat pups can recognize their mothers based solely on maternal calls. We first investigated whether maternal calls of pomona leaf-nosed bats differ statistically among individuals. Then, we tested whether pups recognize their mothers' calls using a playback experiment. Echolocation pulses and directive calls of mother bats contain enough individual characteristics to allow for individual discrimination. Playback experiments showed that the pups responded with more vocalizations to playback of their own mother's versus another mother's directive calls, but not to playback of their own mother's versus another mother's echolocation pulses, suggesting that offspring can distinguish directive calls, but not echolocation pulses, of their own mother from those of other mothers. To our knowledge, this is the first study in which directive calls from bat mothers have been used to elicit vocalizations from pups and the first study to indicate that pups can recognize their mothers based solely on directive calls. These results advance our understanding of the function of acoustic signals in mother–offspring recognition and the adaptive benefit of such communication, particularly the conditions under which a pup's recognition of its mother is critical. Highlights: There is a debate about whether or not bat pups recognize their mother's calls. We demonstrated that directive calls and echolocation pulses are unique to individuals. We played maternal directive calls and echolocation pulses to elicit pup responses. Pups recognized directive calls, but not echolocation calls, of their mother. This adds to our understanding of acoustic signals in mother–offspring recognition.